Indoor Propagation Channel Models For Wireless Lan Based On 802.11b Standards At 2.4 Ghz Ism Band - Sujak, Bahrin (2007)

(untitled)
The WLAN is a preferred choice of technology for internet connection in the building environment. The indoor models, reported in the literature are mostly studied in the 900 MHz band of cellular standard and quite scarce in the 2.4 GHz frequency band of WLAN 802.11 standard. The frequency band is also dedicated for the WiMAX technology in which deployment in the office environment is essential. In this thesis, the semi-empirical indoor Multi Wall Classic Extended (MWCE) channel model is proposed. The model is compared and evaluated with the empirical OS and other semi-empirical Multi Wall models obtained from the literature; the Multi Wall Classic (MWC) and Multi Wall Linear (MWL). The models are evaluated based on the accuracy of prediction at two floors of office environment in one of the telecommunication company building. The validity of the proposed model is evaluated through comparison with different models of similar type from the literature. The optimized model coefficients for all models, particularly for the wood/glass and brick/concrete the common wall obstacles in the building, are found. The behavior and characterization of all the models studied are investigated by evaluating the variation of the prediction error at several locations of the same propagation condition. The prediction from the MWCE model is significantly improved compared to the OS model. The MWCE model is also observed to have a high and consistent accuracy prediction, comparable with the MWC and MWL models. The accuracy of the MWCE model is also shown to compare closely with different models of similar type from the literature. With simple formulation without invoking too many details and high consistent accuracy prediction, the proposed MWCE model is suitable for prediction of WLAN signal in the indoor environment to be incorporated in the software planning tool.